Betaine Delayed Muscle Loss by Attenuating Samtor Complex Inhibition for mTORC1 Signaling Via Increasing SAM Level - Chen, Si; Lu, Xiao‐Ting; He, Tong‐Tong; Yishake, Dinuerguli; Tan, Xu‐Yin; Hou, Meng‐Jun; Luo, Yun; Long, Jing‐An; Tang, Zhi‐Hong; Zhong, Rong‐Huan; Fang, Ai‐Ping; Zhu, Hui‐Lian (Molecular nutrition & food research, 2021)
Scope The muscle loss during aging results from the blunt of protein synthesis and poses threat to the elderly health. This study aims to investigate whether betaine affects muscle loss by improving protein synthesis. Methods and Results Male C57BL/6J mice are raised from age 12 or 15 months. Mice are fed with AIN‐93M diet without or with 2% w/v betaine in distilled water as control group or betaine intervention group (Bet), respectively. Betaine supplementation to mice demonstrates better body composition, grip strength, and motor function. Muscle morphology upregulates expression of myogenic regulate factors, and elevates myosin heavy chain and also improves in Bet group. Betaine promotes muscle protein synthesis via tethering mammalian target of rapamycin complex1 protein kinase (mTORC1) on the lysosomal membrane thereby activating mTORC1 signaling. All these effects aforementioned are time‐dependent (p < 0.05). Ultrahigh‐performance liquid chromatography results show that betaine increases S‐adenosyl‐l‐methionine (SAM) via methionine cycle. SAM sensor—Samtor—overexpression in C2C12 cells could displace mTORC1 from lysosome thereby inhibiting the mTORC1 signaling. Addition of betaine attenuates this inhibition by increasing SAM level and then disrupting interaction of Samtor complex. Conclusions These observations indicate that betaine could promisingly promote protein synthesis to delay age‐related muscle loss. Betaine is a methyl donor in methionine cycle. The present study shows that betaine increases SAM level thereby attenuating Samtor complex inhibition for mTORC1 signaling to delay age‐related muscle loss and promotes C2C12 cells differentiation. The findings of the study indicate that betaine is a promising nutrition input upstream mTORC1 signaling for the elderly to delay the age‐related muscle loss.